To solve the quadratic equation 2m^2 - 5m + 3 = 0 using the factorization method, we need to factorize the quadratic expression and set each factor to zero.
The equation can be rewritten as:
2m^2 - 3m - 2m + 3 = 0
Now, let's factorize the expression:
m(2m - 3) - 1(2m - 3) = 0
Now, we have two factors: (2m - 3) and (m - 1). Setting each factor to zero and solving for m:
2m - 3 = 0 or m - 1 = 0
Solving these equations gives us:
2m = 3 or m = 1
Dividing both sides by 2:
m = 3/2 or m = 1
Therefore, the solutions to the quadratic equation 2m^2 - 5m + 3 = 0 are m = 3/2 and m = 1.
Solve the quadratic equation using factorisation method: 2m^2-5m+3=0
1 answer